Inclusive Consumption: Immigrants’Access to and Use of Public and Private Goods and Services 2019
DOI: 10.18261/9788215031699-2019-03
|View full text |Cite
|
Sign up to set email alerts
|

3. Uniformity Without Uniforms: Dressing School Children in Norway

Abstract: This chapter discusses the relationship between Norwegian schools' ideals of equality and the way in which school clothes are regulated. Interviews with a teacher in a transitional language learning group for newly arrived immigrant children, as well as with children and parents in immigrant families, are used to discuss whether school clothes inhibit or promote integration. The material shows great willingness of children to dress like the others, as well as understanding that clothing consumption is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A study from Turkey revealed other important factors such as size of garment, price, quality, easy trade and payment options (Köksal, 2007). Some studies apply consumption theory to investigate how parents as consumers have a very specific role regarding their children's consumption (Klepp, Laitala, & Skuland, 2019;Storm-Mathisen, 2008). Thus, children's influence on household consumption is an important part of how consumption practices should be approached.…”
Section: Ingun Grimstad Klepp and Vilde Haugrønningmentioning
confidence: 99%
See 3 more Smart Citations
“…A study from Turkey revealed other important factors such as size of garment, price, quality, easy trade and payment options (Köksal, 2007). Some studies apply consumption theory to investigate how parents as consumers have a very specific role regarding their children's consumption (Klepp, Laitala, & Skuland, 2019;Storm-Mathisen, 2008). Thus, children's influence on household consumption is an important part of how consumption practices should be approached.…”
Section: Ingun Grimstad Klepp and Vilde Haugrønningmentioning
confidence: 99%
“…Children are outdoors regardless of weather and season, and the Nordic climate with its varying weather during all four seasons, demands clothing that can protect the child from being cold and wet and that enables movement. Kindergartens and schools have certain demands for clothes, both the ability to stay dry and warm and the amount of clothes (Klepp et al, 2019). Purchasing children's clothing, such as winter overalls and outdoor jackets, is expensive and can therefore be seen as a risk to the household economy if the garment is worn out faster than the child grows out of it (Klepp et al, 2019;Rutanen, Raittila, & Vuorisalo, 2019).…”
Section: Dressing Children In a Nordic Climatementioning
confidence: 99%
See 2 more Smart Citations